Chinese breast cancer patients with CYP2D6*10 mutant genotypes have a better prognosis with toremifene than with tamoxifen. Issue 2 (30th June 2021) - Wang, Hongyue; Ma, Xinchi; Zhang, Bin; Zhang, Yaotian; Han, Ning; Wei, Linlin; Sun, Chaonan; Sun, Shichen; Zeng, Xue; Guo, Hong; Li, Yubing; Zhang, Yanyu; et al.
Abstract: Purpose: To evaluate the prognosis of estrogen receptor‐positive breast cancer patients with CYP2D6*10 mutant genotypes under tamoxifen or toremifen therapy. Methods: Estrogen receptor‐positive breast cancer patients were selected and CYP2D6*10 genotypes (C/C, C/T, and T/T) were determined by Sanger sequencing. Patients were divided into tamoxifen, toremifene, or tamoxifen + toremifene groups according to prior therapy. The correlation between CYP2D6*10 genotype and disease‐free survival was analyzed. Results: In total, 293 estrogen receptor‐positive breast cancer patients treated with tamoxifen or toremifene between 2008 and 2017 were studied. Median follow‐up was 39 months (10–141). Of these, 107 (36.52%), 112 (38.23%), and 74 (25.26%) patients had C/C, C/T, and T/T genotypes, respectively. Genotype was significantly associated with disease‐free survival in tamoxifen patients. Patients with C/T and T/T genotypes showed worse disease‐free survival than patients with a C/C genotype. Genotype and disease‐free survival in toremifene and tamoxifen+toremifene patients were not correlated. Of patients with a C/T genotype, toremifene or tamoxifen+toremifene groups showed better disease‐free survival than tamoxifen patients. Although disease‐free survival of patients with a T/T genotype in the three groups was not statistically different, tamoxifen patients showed worse disease‐free survival. There was no correlation between different treatments and disease‐free survival in patients with a C/C genotype. Cox proportional hazard analysis revealed toremifene patients had a better prognosis than tamoxifen patients; toremifene was an independent protective factoremifene for disease‐free survival. Conclusions: Tamoxifen was less effective in patients with CYP2D6*10 C/T and T/T genotypes. Estrogen receptor‐positive breast cancer patients with a CYP2D6*10 mutation genotype have a better prognosis with toremifen than tamoxifen. Abstract : DFS of patients with different genotypes in the TAM, TOR and TAM+TOR group. TAM tamoxifen, TOR toremifene, DFS disease‐free survival, C/C wild‐type CYP2D6 *10, C/T heterozygous CYP2D6 *10, T/T mutant CYP2D6 *10